2006
DOI: 10.1007/s11249-006-9117-5
|View full text |Cite
|
Sign up to set email alerts
|

Shape and texture features in the automated classification of adhesive and abrasive wear particles

Abstract: In this study the automated classification system, developed previously by the authors, was used to classify wear particles. Two kinds of wear particles, adhesive and abrasive, were classified. The wear particles were generated using a pin-on-disk tribometer. Various operating conditions of load, sliding time and abrasive grit size were applied to simulate adhesive and abrasive wear of different severity. SEM images of wear particles were acquired, forming a database for further analysis. The particle images w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…1, the natural logical process to construct an automatic ferrography system is linear, including the following steps: image preprocessing →wear particle segmentation →feature extraction →wear particle recognition →wear condition detection. Various image processing techniques, such as image segmentation [8][9][10][11], feature extraction [12,13], and classification methods [14][15][16][17][18][19], have been applied to wear particle analysis.…”
Section: Introductionmentioning
confidence: 99%
“…1, the natural logical process to construct an automatic ferrography system is linear, including the following steps: image preprocessing →wear particle segmentation →feature extraction →wear particle recognition →wear condition detection. Various image processing techniques, such as image segmentation [8][9][10][11], feature extraction [12,13], and classification methods [14][15][16][17][18][19], have been applied to wear particle analysis.…”
Section: Introductionmentioning
confidence: 99%
“…42 Also, the method could be extended to work on 3D images such as MRI and used, for example, in the characterisation of brain tumors. 43 Possible applications in engineering could be found in determination of the condition status of a mechanical system and prediction of machine failure, [44][45][46] determination of a relationship between surface texture and coefficient of friction, 47 and multiscale characterisation of 3D engineering surfaces. 48 However, there is a limitation in use of our methods.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed information on the feature extraction columns separately and downsampling by two (32) method incorporated in the automated classification [47]. This produced both approximated (LL) and detail images (LH, HL, HH ) used in this study can be found in reference [25] and on the dimension reduction technique in reference [26]. The methods used in this work are briefly…”
Section: Pattern Recognition Methodsmentioning
confidence: 99%
“…Larger images are usually recommended tures such as clusters of chondrocytes surrounded by the amorphous matrix [55]. Although these sub-in pattern recognition to avoid classifying of insignificant features, as previous studies have shown surface cartilage images are different to the ESEM images of unworn top cartilage surfaces analysed [25,26].…”
Section: Texture-based Classification Of Worn Cartilagementioning
confidence: 99%